Pengaruh Literasi Ekonomi Terhadap Perilaku Konsumtif Mahasiswa Pendidikan Akuntansi - Nova Pratiwi; Chandra Kurniawan; Riswan Aradea (Universitas Negeri Surabaya, 2023)
This study analyzes the effect of economic literacy on student consumptive behavior, using a quantitative research approach with survey methods. The research data was collected by distributing questionnaires, the research respondents were 70 undergraduate students of the accounting education study program who were drawn by purposive sampling, and the analysis of research data used simple regression with prerequisite tests for data normality and linearity analysis. The results of the study revealed that the level of economic literacy of students was quite diverse, but around 54% were at a moderate literacy level. Student consumptive behavior tends to be moderate, namely around 60% of the respondents. The results of the hypothesis test reveal that economic literacy has a negative influence on student consumptive behavior. This indicates that students have self-awareness of the ability to buy a product, buy products according to their needs, and can manage personal finances to save.